Carica Papaya Agribusiness Development Strategy in Wonosobo District - Nasiron Nasiron; Suhendar Sulaeman; Liza Nora (Business Review and Case Studies, 2024)
Background: In Dieng, wich is the border of Banjarnegara and Wonosobo, there are up to 67.000 carica papaya trees with a production capacity of over 119 in 2021, so that industrial businesses in the horticultural agricultural sector have great opportunities to develop. Purpose: The aim of this research was to identify existing constraints from both internal and external distribution factors so that a distribution strategy could be found to increase overall sales volume.Design/methodology/approach: The data analysis technique was Strengths, Weaknesses, Opportunities & Threats (SWOT).Findings/results: Meanwhile, the case study methodology used ten informants as sources. The IFAS calculation result was 0.27, and the EFAS calculation result was 0.08. The main implication of the results of this research showed that the implementation of an effective distribution strategy, including licensing and infrastructure improvements, could significantly boost revenue from sales of typical food and beverages in Wonosobo.Conclusion: Plan to grow sales volume in Wonosobo Regency’s carica papaya horticultural industry, emphasizing distribution permit ownership, facility and infratructure upgrades, and certification to guarantee client enjoyment and safety. Getting a distribution permit requires upgrading production facilities and infrastructure, which will boost consumer confidence and enable effective distribution strategies to boost sales.Originality/value (State of the art): An effective and efficient distribution Strategy will Increase Sales of Processed Carica Fruit Products in Wonosobo. Keywords: carica papaya, agribusiness development, development strategy, swot, distribution factors